The role of zeolite in imparting bacteriostatic properties to paper - V. G. Tsitsishvili; N. M. Dolaberidze; M. K. Doula; O. T. Gemishev; N. A. Mirdzveli; M. O. Nijaradze; Z. S. Amiridze; B. T. Khutsishvili (Хімія, фізика та технологія поверхні)
The introduction of zeolite fillers containing silver, copper, zinc, etc. into paper gives it bacteriostatic properties. The purpose of this work was to clarify the role of zeolite and to elucidate the possibility of imparting antimicrobial properties to packaging paper more simply by introducing into the paper pulp not ready-made zeolite fillers, but mixtures of zeolite and a salt of the corresponding metal. The experiments used heulandite-bearing tuff from the Dzegwi-Tedzami deposit (Eastern Georgia) and its amorphized form, as well as salts - silver nitrate, copper chloride dihydrate and zinc chloride; the paper was made in laboratory. It has been found that the introduction of silver nitrate into paper pulp leads to the reduction of silver ions and the formation of Ag0 nanoparticles with average size of 38 nm, which is facilitated by the introduction of crystalline zeolite. Copper chloride dihydrate introduced into paper pulp forms both large (> 200 nm) crystallites and nanoparticles (< 20 nm), zinc chloride forms nanoparticles. Bacteriostatic properties of paper samples were tested by the disk diffusion method using the cultures of Gram-negative bacteria Escherichia coli and Salmonella enteritidis, Gram-positive bacteria Staphylococcus aureus and Bacillus subtilis, fungal pathogenic yeast Candida albicans and a fungus Aspergilus niger. Silver-containing paper without zeolite fillers has the lowest activity, and with the introduction of fillers, zinc-containing paper demonstrates the highest activity against all microorganisms. Crystalline zeolite filler enhances the effect of silver against Salmonella and Bacillus subtilis, while amorphous filler enhances the effect of zinc against Gram-positive bacteria and fungi; both zeolite fillers weaken the action of copper.